Analyses of Business Attributes and Facebook Utilization: Marketing Insights - Ma. Charity Reign Dela Cruz; Louis Yucci C. Voluntad; Karl Vince B. Saranillo (International Journal of Marketing and Digital Creative, 2024)
Microenterprises have a significant impact on the nation's economic development. Given the current trends in marketing, numerous organizations have adopted social media marketing. This study analyzed Facebook's business attributes and perceived effectiveness as an advertising tool for microenterprises. The researchers employed a descriptive-causal research design through random sampling of 320 registered microenterprises that utilize Facebook as an advertising tool. Findings revealed that participants were mostly under sole proprietorship, having one to three employees with an estimated asset size of less than 1,000,000 pesos and being in operation for one to three years. Customer brand awareness, product promotion, engagement reach, and sales volume were found to be highly effective in the perceived effectiveness of Facebook use. Remarkably, the business profile length of operation showed significant differences in terms of volumes of sales, whereas the number of staff in terms of customer brand awareness, engagement reach, and volume of sales; average asset size in terms of customer brand awareness and product promotion indicated significant differences to the perceived effectiveness of Facebook utilization as an advertising platform. Hence, the researchers recommended that microenterprises focus on targeted advertising, allocating advertising investment, and optimizing Facebook's advertising features.